2011
DOI: 10.1007/s10140-010-0932-5
|View full text |Cite
|
Sign up to set email alerts
|

The value of a CT scan compared to plain radiographs for the classification and treatment plan in tibial plateau fractures

Abstract: This study aimed to evaluate the intra- and interobserver agreement for both fracture classification according to Schatzker and treatment plan of tibial plateau fractures using plain radiographs alone and with computed tomography (CT) scans. The study was carried out prospectively to assess the impact of an advanced radiographic study on the agreement of treatment plan and fracture classification of tibial plateau fractures. Eight experienced observers (six surgeons and two radiologists) classified 15 tibial p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(26 citation statements)
references
References 11 publications
(13 reference statements)
1
24
1
Order By: Relevance
“…Our study yielded comparable interobserver (κ XR =0.51; κ CT =0.61) and intraobserver (κ XR = 0.58; κ CT =0.66) results to those of Brunner et al [10] (κ XR =0.418; κ CT =0.755). This was slightly better than the quoted mean κ CT of 0.61 from several other studies [8,11,12] but worse than findings of Brunner et al [10] and Hu et al [13] The clinical experience has been suggested to affect the interobserver reliability between observers with different level of experience; [10,14] however, our study findings contradicted with this, with no significant differences found among the observers despite differences in experience.…”
Section: Discussioncontrasting
confidence: 92%
“…Our study yielded comparable interobserver (κ XR =0.51; κ CT =0.61) and intraobserver (κ XR = 0.58; κ CT =0.66) results to those of Brunner et al [10] (κ XR =0.418; κ CT =0.755). This was slightly better than the quoted mean κ CT of 0.61 from several other studies [8,11,12] but worse than findings of Brunner et al [10] and Hu et al [13] The clinical experience has been suggested to affect the interobserver reliability between observers with different level of experience; [10,14] however, our study findings contradicted with this, with no significant differences found among the observers despite differences in experience.…”
Section: Discussioncontrasting
confidence: 92%
“…Recently, several studies concluded that a multiplanar CT scan enhances the reliability in classifying tibial plateau fractures [9-12]. Compared to the conventional AO and Schatzker classification, a CT-based three-column classification as applied in our study is associated with substantial agreement amongst independent observers [8].…”
Section: Discussionmentioning
confidence: 59%
“…Previous studies of other anatomic areas are conflicting when comparing interobserver agreement among imaging modalities [5,22]. For example, Brunner et al [5] found higher reliability of tibia plateau fracture classification on CT images with radiographs compared with radiographs alone, whereas te Stroet et al [22] did not find a difference in reliability for classification and treatment recommendation between CT images and radiographs for these fractures. This discrepancy might be explained by the relatively low number of observers, inclusion of different fracture subtypes, and difference in quality of the imaging.…”
Section: Discussionmentioning
confidence: 99%
“…Studies of fractures at other anatomic areas (such as the tibia plateau) are conflicting regarding improved fracture assessment reliability when comparing CT scans with radiographs [5,6,22]. Criteria used for diagnosis or treatment ideally should be reliable, accurate, and associated with outcome.…”
Section: Introductionmentioning
confidence: 99%